Studies of Mixed Solid Waste in Reference to Biomedical Waste: Effective Management and Strategic Actions (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Within the domain of municipal solid wastes, bio-medical wastes acquire a special dimension, since it is infected and hazardous. In hospitals and health care facilities, waste generated differs from municipal waste in general. Only one of these collection, transport and final disposal systems which be needed by municipal wastes in general. This could involve more structures, as they include parts of the body, human tissues and animal tissues, toxic wastes, gaze, cotton, plastics, liquid waste contaminated, blood and wastes from laboratories. This paper provides comprehensive discussion on mixed solid waste in reference to Biomedical Waste and makes some recommendations for their effective management besides discusses the key strategic actions required for an effective bio-medical waste management plan preparation.